Proper Calibration of Soil Fumigant Application Equipment - Joseph W. Noling; J. P. Gilreath (EDIS)
This document is ENY-047, one of a series of the Entomology & Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: February 2002.